Nutritional biochemistry - Sharma, DC; Sharma, Devanshi (New Delhi : CBS Publishers & Distiributors Pvt. Ltd., 2017)
Nutritional biochemistry is meant for student of BSc (nutrition) and BSc (home science) courses who require fundamental knowledge of biochemistry with emphasis on food sources of all the nutrients like carbohydrates, proteins, fats, lipids, vitamins and minerals.
Chemistry of carbohydrates -- Chemistry of amino acids and proteins -- Chemistry of lipids -- Vitamins -- Minerals -- Enzymes -- Carbohydrate metabolism -- Protein metabolism -- Amino acid metabolism -- Lipid metabolism -- Chemistry and metabolism of nucleic acids -- Energy metabolism (Biological oxidation) -- Antioxidants -- Dietary fiber -- Toxicants present on food.
original published in 2015.
Include Index.
Keywords: Biochemistry; Vitamins; Minerals; Enzymes; Chemistry